The human boy and the war - Phillpotts, Eden (The Macmillan Company, 1916)
The battle of the sand-pit.--The mystery of Fortescue.--The countryman of Kant.--Travers minor, scout.--The Hutchings testimonial.--The fight.--Percy minimus and his Tommy.--The prize poem.--The revenge.--The "Turbot's" aunt.--Cornwallis and me and fate.--For the Red cross.--The last of Mitchell.